Kemanfaatan Hukum “Peran Pejabat Pembuat Akta Tanah” Dalam Upaya “Peralihan Hak Tanah Ulayat” oleh “Anggota Masyarakat Adat” Daerah Pora Nusa Tenggara Timur - Melfijanti Melfi; M. Ryan Bakry; Frengki Hardian (Publikasi Indonesia, 2022)
The position of indigenous peoples is basically recognized by the Indonesian nation with diversity in Indonesia which is a reflection of Bhinneka Tunggal Ika and also this recognition is contained in the amendment to the basic law